The Important Role of Volatile Components From a Traditional Chinese Medicine Dayuan-Yin Against the COVID-19 Pandemic - Zhang, Xiao-rui; Li, Ting-na; Ren, Yuan-yuan; Zeng, Yi-jia; Lv, Hong-yang; Wang, Jin; Huang, Qin-wan (Frontiers in Pharmacology, 2020)
Aromatic Chinese herbs have been used to prevent plagues since ancient times. Traditional Chinese medicine has unique advantages in the prevention and treatment of epidemic diseases. According to the traditional Chinese medicine treatment plan in the National COVID-19 Diagnosis and Treatment Plan (Trial Seventh Edition) of the National Health Commission, Chinese patent medicines or prescriptions rich in aromatic Chinese herbs are selected for prevention and treatment during the period of medical observation, clinical treatment, and recovery of confirmed COVID-19 patients. Some local health committees or traditional Chinese medicine administrations recommend a variety of other ways of using traditional aromatic Chinese herbs to prevent and cure COVID-19. These involve external fumigation, use of moxibustion, and wearing of sachet. The efficacy of aromatic Chinese herbs plays a decisive role in the prevention and treatment of COVID-19. The unique properties, chemical composition, and mechanism of action of aromatic Chinese herbs are worthy of extensive and in-depth experimental and clinical research. The findings are expected to provide a reference for follow-up treatment of novel coronavirus and the development of corresponding drugs. In 2003, Dayuan-Yin produced excellent results in the treatment of the SARS virus. Individually, 112 confirmed cases were administered this drug between January and April 2003, and more than 93.7% of the patients showed noticeable mitigation of the symptoms, as well as recovery. Dayuan-Yin also was selected as one of the nationally recommended prescriptions for the COVID-19. Based on the national recommendation of Dayuan-Yin prescription, this review discusses the role of volatile components in the prevention and treatment of COVID-19, and speculates the possible mechanism of action, so as to provide a basis for the prevention and treatment of COVID-19.